Pilihan Bahasa Bali pada Komunitas Usia Muda di Kelurahan Monjok Barat Kecamatan Nusa Tenggara Barat - Oktarini, Putu; Dhananwaty, Ni Made; Suryati, Ni Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
The study, entitled “Selection of Balinese language in Young People community Monjok Barat Village,  Selaparang District, Nusa Tenggara  Barat” is explained how to the speech selection of Balinese language in young people community Monjok  Barat village in choosing the language to interact  with  domain  different people  in  a variety  of  interest that exits. The research aims at describing  the  language choosing the speech Bali community. The  theories used in this study are speech community theory stated language choice of theory by Fasold .  Source of data obtained from  the speech at  the event said in the family realm, social realm, employment realm, religious  realm, art  realm. The technique  used to process the data that refer to the  method  and  competent method. Data analysis  used to process the data that distribusional method or agih method and padan method. The technique and method presentation of  analysis result used to formal method and informal method.  The research finds the occurrence selection of language in 5 realm are family realm, social realm, religious realm, employment realm and art realm. Selection of language used  by young people  have difference in each realm.  The  selection of  language used by generation of young people uses Indonesian language more  than Balinese language,